Smithsonian Folkways Recordings: The Role of Music in Breaching the Barriers of the Box. (October 2014) - Sheehy, Daniel
Abstract Smithsonian Folkways Recordings is the nonprofit record label of the Smithsonian Institution, the United States national museum. Folkways pairs with the Smithsonian's annual Folklife Festival in honoring and bringing to public attention the keepers of intangible cultural heritage traditions from many parts of the world. At the Folklife Festival, which takes place on the National Mall in Washington, D.C. each summer, the culture bearers speak for themselves in a presentational environment designed to promote interaction among the participants and audience members. In 2011, Folkways recordings of regional music from Colombia sparked an entire Folklife Festival program.